Molecular detection of potential sexually transmitted pathogens in semen and urine specimens of infertile and fertile males - Abusarah, Eman A.; Awwad, Ziad M.; Charvalos, Ekatherina; Shehabi, Asem A. (Diagnostic microbiology and infectious disease, 2013)
A total of 93 infertile and 70 fertile men attending various urology and gynecology clinics in Jordan were investigated in this prospective study. First void urine and the corresponding semen specimens were collected from 96% of the patients. Presence of Neisseria gonorrhoeae (NG), Chlamydia trachomatis (CT), Ureaplasma urealyticum (UU), and Mycoplasma genitalium (MG) DNA in specimen was detected using polymerase chain reaction. The distribution of NG, CT, UU, and MG in semen and FVU specimens among infertile versus fertile men was 6.5% versus 0%, 4.3% versus 1.4%, 10.8% versus 5.7%, and 3.2% versus 1.4%, respectively. Two of infertile and 1 of fertile men harbored mixed pathogens. The highest number of positive potential pathogens was found among young men aged 20–29 years old. The present study found a very high concordance between the detection of CT, UU, and MG DNA in semen and the corresponding FVU specimens, while NG DNA found only in semen and not in the corresponding FVU specimens. This study also revealed that Ureaplasma parvum species is more prevalent than Ureaplasma urealyticum in specimens of infertile men (90%). The study demonstrates that infertile men have higher prevalence of NG, CT, UU, and MG compared with fertile men and NG as significantly associated with infertile men.